2022
DOI: 10.1093/molbev/msac251
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Speciation Promoted by Divergent Regulation of Functional Genes Within African Cichlid Fishes

Abstract: Rapid ecological speciation along depth gradients has taken place repeatedly in freshwater fishes, yet molecular mechanisms facilitating such diversification are typically unclear. In Lake Masoko, an African crater lake, the cichlid Astatotilapia calliptera has diverged into shallow littoral and deep benthic ecomorphs with strikingly different jaw structures within the last 1,000 years. Using genome-wide transcriptome data, we explore two major regulatory transcriptional mechanisms, expression and splicing QTL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 112 publications
(223 reference statements)
1
15
0
Order By: Relevance
“…Given ecotype divergence at many – at least a hundred or so – genomic loci (Malinsky et al 2015), we could expect that recombination, or the lack thereof, would be important in bringing together and keeping together the alleles that are beneficial in each environment (Ortiz-Barrientos et al 2016; Todesco et al 2020; Schluter and Rieseberg 2022; Battlay et al 2023). Our findings reveal and characterize substantial differences in population recombination rates between the ecotypes, complementing previous studies of divergence in ecology, mate choice, and allele frequencies (Malinsky et al 2015), methylation (Vernaz et al 2022), gene expression (Carruthers et al 2022), and in sex determination (Munby et al 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Given ecotype divergence at many – at least a hundred or so – genomic loci (Malinsky et al 2015), we could expect that recombination, or the lack thereof, would be important in bringing together and keeping together the alleles that are beneficial in each environment (Ortiz-Barrientos et al 2016; Todesco et al 2020; Schluter and Rieseberg 2022; Battlay et al 2023). Our findings reveal and characterize substantial differences in population recombination rates between the ecotypes, complementing previous studies of divergence in ecology, mate choice, and allele frequencies (Malinsky et al 2015), methylation (Vernaz et al 2022), gene expression (Carruthers et al 2022), and in sex determination (Munby et al 2021).…”
Section: Discussionsupporting
confidence: 84%
“…The impact of post-transcriptional processing on adaptation is a small but growing field of research. Many previous studies have focused on a particular phenotype associated with alternative splicing in a single gene (Gacheva et al 2011;Jarosch et al 2011;Howes et al 2017;Ceinos et al 2018). In contrast, we looked for signatures of adaptive, alternative splicing genome-wide.…”
Section: Discussionmentioning
confidence: 99%
“…Heritable variation in gene expression is a well-known source of adaptive evolution but has been primarily studied in the context of transcript abundance. Nonetheless, there is an increasing recognition of the importance of post-transcriptional regulation, and a handful of studies have used genome-wide short-read RNA-Seq to study mRNA abundance in conjunction with alternative splicing in the context of local adaptation (Huang et al 2021;Jacobs & Elmers 2021;Carruthers et al 2022;Singh et al 2022;Steward et al 2022;Huang et al 2023). Several patterns have emerged from these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression plays an important role in ecological speciation and can be an early indicator of species divergence (Wolf et al., 2010). Divergence in gene expression can contribute to hybrid speciation via niche specialization, reproductive isolation from parent species or both (Carruthers et al., 2022; Pavey et al., 2010; Renaut et al., 2009). It has also been suggested that gene expression plasticity could be important for species to adapt to climate change (Kelly, 2019), however climate imposed selection can potentially reduce that plasticity (Kelly et al., 2017).…”
Section: Introductionmentioning
confidence: 99%